Experimental analysis on behaviour in waves for sandglass-type floating body. (3rd April 2017) - Wang, Wen-hua; Du, Ya-zhen; Wang, Lin-lin; Yao, Yu-xin; Gao, Hao; Huang, Yi
Abstract: In order to solve the performance limitations of traditional ship-type and cylindrical FPSO, this paper describes a new concept of sandglass-type floating body. In order to verify the performance advantages of the new concept of design, a series of tests with the sandglass-type and cylindrical floating models were carried out, which include free decay, regular and irregular wave experiments. Finally, the characteristic of natural period, viscous damping and motion response for the new sandglass-type model was studied. By comparing the experimental results of the two floating models, some useful conclusions can be made as follows: the design of sandglass-type shape floating body can significantly improve the heave motion performance of FPSO and can be considered as an attractive alternative system in deep water for offshore petroleum exploration.